Dissecting the causal relationship between moderate to vigorous physical activity levels and cognitive performance: a bidirectional two-sample Mendelian randomization study - Fang, Qi; Zhang, Jinmin (Frontiers in Psychology, 2024)
Recent studies increasingly suggest that moderate-to-vigorous physical activity (MVPA) impacts cognitive risk. However, the bidirectional nature of this relationship warrants further exploration. To address this, we employed a Mendelian randomization (MR) approach, analyzing two distinct samples.Methods: These analyses utilized published Genome-wide association study (GWAS) summary statistics for MVPA (n=377,234) and cognitive performance (n=257,841). Our primary method was the inverse variance weighted (IVW) model with random effects, aiming to deduce potential causal links. Additionally, we employed supplementary methods, including MR Egger regression, Weighted median, Weighted mode, and Simple mode. For sensitivity analysis, tools like the MR Egger test, Cochran's Q, MR PRESSO, and leave-one-out (LOO) were utilized.[OR]=0.577, 95% Confidence Interval [CI]: 0.460-0.723, p=1.930 × 10-6). Furthermore, enhanced cognitive levels corresponded to a reduced risk of inadequate MVPA (OR=0.866, 95% CI: 0.839-0.895, p=1.200 × 10-18).Discussion: In summary, our study demonstrates that MVPA lowers cognitive risk, while poor cognitive health may impede participation in MVPA. Overall, these findings provide valuable insights for developing personalized prevention and intervention strategies in health and sports sciences.